Diffusional flow under non-isothermal laminar free convection : II. Experimental approach - Marchiano, Susana Lucy (1969)
The rate of a non-isothermal free convection process has been measured at different temperature gradients in an electrochemical cell having parallel vertical plate copper electrodes, the reaction being the electrodeposition of copper from a copper-sulphate-sulphuric-acid solution. Results agree with the theoretical equation derived previously. They are correlated in a way similar to isothermal free convection in terms of dimensionless ratios, and an equivalence between thermal gradient and rate of stirring under laminar forced convection is established.